Oral communication strategies among international students at UKM - Tan, Kim Hua; Nor Fariza Mohd Nor; Mohd Nayef Jaradat (Penerbit UKM, 2012)
This study investigated how and when oral communication strategies are used in group discussions by international students at Universiti Kebangsaan Malaysia, a public university in Malaysia. It aims to examine the differences in the use of communication strategies between high and low proficient speakers. The participants were a group of ten low proficient Arabic speakers of English and a group of ten high proficient Chinese and Arabic speakers of English. Data elicited from audio recordings of oral group discussions and a self-report questionnaire was used to identify communication strategies used. The findings showed that the subjects resorted to ten out of the twelve types of communication strategies specified by Tarone (1980), Faerch and Kasper (1983), and Willems (1987). The most frequently employed communication strategy was code switching; an interlingual strategy and the least used strategy was word coinage; an intralingual strategy. Further investigation indicated that different levels of oral proficiency influenced the use of communication strategies from two aspects. They are the frequency of use and the selection of types of communication strategies. This implies that international students studying at Universiti Kebangsaan Malaysia (UKM) need to be made aware of the use of communication strategies depending on their level of proficiency and the fact that raising the awareness of both low proficient and also high proficient speakers to strategies that are used by speakers of different proficiency levels may well help ease communication.